VMware virtualization fundamentals : learn about the industry leading virtualization platform (Apress, 2023)
In this course, you'll learn the fundamentals of virtualization and also the types of virtualization available. You will then learn the information necessary to create a VMWare vSphere environment and you'll learn the basics of how the vSphere components work. We'll go through the configuration of networking and storage, snapshots, and backups. We'll also work through creating a virtual machine using both templates and clones. After the completion of this course, you'll have an operating VMware vSphere environment for use for whatever purpose you require. This is the first part of 3-course series. What You Will Learn: Understand what virtualization all is about and how virtual machines are configured and deployed Compare and contrast Type 1 and 2 hypervisors Deploy a Virtual Machine on VMware and understand what to configure Who this course is For: Anyone wanting to learn about virtualization and VMWare solutions.